Adolescent males referred for psychotherapy: Examining emotional instability in light of parental identification - Garcia, Washington C. (Animo Repository, 2003)
This is a multiple case, multiple measures study designed to examine the factors that lead to children’s identification with their parents and how such identification in turn impacts on their emotional well-being as adolescents. Only the integrated findings are reported in this paper. Results show that the nine adolescent males referred for psychotherapy all manifest strong emotional attachment to their mothers but only five of them seem to have an adequate bond with their fathers. Data suggests that the attention and affection shown by a parent play a significant part in this process. The limited interaction that the adolescents presently have with both parents does not seem to affect the parental emotional bond, but time spent together when they were younger children is highly connected to their positive impression of each parent. Perception of each parent may be crucial to the adolescent males’ experience of emotional closeness: positive views of mothers persist in spite of the present difficult situation while images of fathers are readily tarnished under the same problematic circumstances. A number of other factors contribute to an adolescent male’s emotional instability. Personal and marital issues of parents are triggered when the boy underperforms in school or manifests behavioral problems. The depressed mother withdraws from parenting and the angry father pressures the boy. The teenage son sees his father as aggravating his difficulties, a negative impression that is reinforced by the boy’s perception that his mother is fearful of and troubled by his father. But a close mother-son relationship may also result in gender identity confusion and suicidal rumination. Negative modeling, on the other hand, may be observed in an adolescent boy who is close to his father.